Fresno County Bar Association Annual Bar Banquet Held at Elks Lodge - Watkins, Howard::::::::: (1981)
Bob Fishman, Donald Fischbach, Ken Fransen, Jim Phillips, Kathy ?. Andy Weiss, Lu Parks, George Strasser, and Howard Zidenberg